Center-Pivot-Irrigated Wheat Cost-Return Budget - O'Brien, Daniel M.; Sartwelle III, James D. (My University, 1996)
This publication projects a budget that reflects expected income and costs based on center-pivot-irrigated wheat production.
MF583_1996_10
Keywords: MF583; Economics; Crops; MF